The Role of Career Self-Efficacy as a Mediator of the Effect of Protean Career Orientation on Career Decisions: (A Study of the Millennial Generation in Surakarta) - Teguh Puji Nugroho; Muhammad Sholahuddin (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This study aims to examine the effect of protean career orientation on career decision-making, with career self-efficacy as a mediating variable, among millennials in Surakarta. A quantitative approach was employed using SEM-PLS analysis, with data collected from 152 respondents selected through purposive sampling. The findings indicate that protean career orientation has a positive and significant effect on both career self-efficacy and career decision-making. In addition, career self-efficacy significantly influences career decisions and has been shown to mediate the relationship between protean career orientation and career decision-making. These results highlight the crucial psychological role of career self-efficacy in strengthening individuals’ confidence and clarity when making career choices. The implications of this research suggest that educational institutions, career counselors, and organizations should design career development programs that foster value-driven career orientation and enhance individuals’ self-efficacy, as these factors are essential for improving the quality of career decision-making among millennials in dynamic labor market conditions.